Effect of sodium mercaptoacetic acid on different antimicrobial disks in the sodium mercaptoacetic acid double disk synergy test for detection of IMP-1 metallo-β-lactamase-producing Pseudomonas aeruginosa isolates in Japan. Issue 1 (January 2019) - Sakanashi, Daisuke; Miyazaki, Narimi; Kawamoto, Yuzuka; Ohno, Tomoko; Yamada, Atsuko; Koita, Isao; Miyajima, Setsuo; Suematsu, Hiroyuki; Hagihara, Mao; Asai, Nobuhiro; Koizumi, Yusuke; Yamagishi, Yuka; et al.
Abstract: We determined the optimal antimicrobial in the sodium mercaptoacetic acid double disk synergy test (SMA-DDST) for the detection of IMP-1-producing Pseudomonas aeruginosa isolates in Japan and evaluated the performance of the test. Fifty-four P. aeruginosa clinical isolates were tested, including 39 IMP-1 producers and 15 non-metallo-β-lactamase (MBL)-producing carbapenem- and ceftazidime (CAZ)-resistant isolates. The SMA-DDST was performed with CAZ, cefepime (CFPM), imipenem (IPM), meropenem (MEPM), doripenem (DRPM), or biapenem (BIPM)-containing disks. The sensitivity of the SMA-DDST with CAZ, CFPM, IPM, MEPM, DRPM, and BIPM was 39/39 (100%), 36/39 (92%), 18/39 (46%), 8/39 (21%), 19/39 (49%), and 36/39 (92%), respectively. The specificity was 15/15 (100%) for all SMA-DDSTs. This suggests that the isolates may have a resistance mechanism other than MBL production for IPM, MEPM, or DRPM. Since the CAZ resistance mechanism in P. aeruginosa is the same as that of CFPM, but differs from that of carbapenems, we conclude that combining CAZ with BIPM SMA-DDSTs can prevent any failure in the detection of IMP-1-producing P. aeruginosa .